Analyzing and Modelling the Corrosion Behavior of Ni/Al2O3, Ni/SiC, Ni/ZrO2 and Ni/Graphene Nanocomposite Coatings - Nazir, M.H.; Khan, Z.A.; Saeed, A.; Bakolas, V.; Braun, W.; Bajwa, R.; Rafique, S. (MDPI, 2017)
A study has been presented on the effects of intrinsic mechanical parameters, such as surface stress, surface elastic modulus, surface porosity, permeability and grain size on the corrosion failure of nanocomposite coatings. A set of mechano-electrochemical equations was developed by combining the popular Butler-Volmer and Duhem expressions to analyze the direct influence of mechanical parameters on the electrochemical reactions in nanocomposite coatings. Nanocomposite coatings of Ni with Al2O3, SiC, ZrO2 and Graphene nanoparticles were studied as examples. The predictions showed that the corrosion rate of the nanocoatings increased with increasing grain size due to increase in surface stress, surface porosity and permeability of nanocoatings. A detailed experimental study was performed in which the nanocomposite coatings were subjected to an accelerated corrosion testing. The experimental results helped to develop and validate the equations by qualitative comparison between the experimental and predicted results showing good agreement between the two.